Factors associated with COVID-19: a comparative case-control study in Benin - KÊDOTÉ, Nonvigon Marius; WACHINOU, Ablo; DARBOUX, Aymeric; PADONOU, Géraud; FONTON, Pérince; LENDZELE, Sevidzem; SARR, Fatou; MAVOUNGOU, Jacques François (One Health & Risk Management, 2022)
Introduction: Although there are several previous publications related to risk factors of COVID-19 infection, in Benin there are very few data to explain the outbreak risk factors.Material and methods: This case-control study, conducted from 14 September to 20 October 2020, aimed to identify the risk factors associated with COVID-19 infection in Benin. Questions on knowledge, attitudes, and practices related to COVID-19, sociodemographic characteristics, nutritional factors, medical history, housing and working conditions of respondents were asked through a questionnaire survey. Bivariate and multivariate logistic regression analyses were conducted to identify the factors associated with COVID-19. The statistical significance was set at 5%.Results: In multivariate logistic regression, no handwashing device installed at the home entrance (ORa = 1.86; 95% CI [1.07-3.21]) or a device delivering only water (ORa = 5.57; 95% CI [1.98-15.65]), using permanently air conditioning at workplaces (ORa = 5.48; 95% CI [2.40-12.57]), less knowledge of protective measures (ORa = 1.41; 95% CI [1.08-1.84]) and no knowledge on the coronavirus incubation period (ORa = 4.19; 95% CI [2.37-7.44]) were identified as risk factors for COVID-19 infection.Conclusions: Based on the findings of this study, a contextual response should prioritize strategies that will raise awareness and population’s knowledge of COVID-19 as well as preventive practices.